The impact of working capital management on firms’ performance: Evidence from manufacturing firms listed in the East African Stock Exchanges - Bulenga, Samson (Mzumbe University, 2024)
A thesis submitted to Mzumbe University in partial fulfillment of the requirements for the award of Degree of Masters of Science (MSc) in Accounting and Finance of Mzumbe University